We will learn how to find the equation of a circle through the intersection of two given circles.
The equation of a family of circles passing through the intersection of the circles P\(_{1}\) = x\(^{2}\) + y\(^{2}\) + 2g\(_{1}\)x + 2f\(_{1}\)y + c\(_{1}\) = 0 and P\(_{2}\) = x\(^{2}\) + y\(^{2}\) + 2g\(_{2}\)x + 2f\(_{2}\)y + c\(_{2}\) = 0 is P\(_{1}\) + λP\(_{2}\) = 0 i.e., (x\(^{2}\) + y\(^{2}\) + 2gx\(_{1}\) + 2fy\(_{1}\) + c\(_{1}\)) + λ(x\(^{2}\) + y\(^{2}\) + 2g\(_{2}\)x + 2f\(_{2}\)y + c\(_{2}\)) = 0, where λ (≠ -1) in an arbitrary real number.
Proof:
Let the equations of the given circles be
P\(_{1}\) = x\(^{2}\) + y\(^{2}\) + 2g\(_{1}\)x + 2f\(_{1}\)y + c\(_{1}\) = 0 ………………………..(i) and
P\(_{2}\) = x\(^{2}\) + y\(^{2}\) + 2g\(_{2}\)x + 2f\(_{2}\)y + c\(_{2}\) ………………………..(ii)
Consider the equation P\(_{1}\) + λP\(_{2}\) = 0 i.e., the equation of any curve through the points of intersection of the circles (1) and (2) is
(x\(^{2}\) + y\(^{2}\) + 2g\(_{1}\)x + 2f\(_{1}\)y + c\(_{1}\)) + λ(x\(^{2}\) + y\(^{2}\) + 2g\(_{2}\)x + 2f\(_{2}\)y + c\(_{2}\)) = 0 ………………………..(iii)
Clearly, it represents a circle for all values of λ except λ = -1. For λ = -1 (iii) becomes a first degree equation in x, y which represents a line. In order to prove that it passes through the points of intersection of the two given circles, it is sufficient to show that their points of intersection satisfy (iii).
Let (x\(_{1}\), y\(_{1}\)) be a point of intersection of the given circles.
Then,
\(\mathrm{x_{1}^{2} + y_{1}^{2} + 2g_{1}x_{1} + 2f_{1}y_{1} + c_{1}}\) and \(\mathrm{x_{1}^{2} + y_{1}^{2} + 2g_{2}x_{1} + 2f_{2}y_{1} + c_{2}}\)
⇒ (\(\mathrm{x_{1}^{2} + y_{1}^{2} + 2g_{1}x_{1} + 2f_{1}y_{1} + c_{1}}\)) + λ(\(\mathrm{x_{1}^{2} + y_{1}^{2} + 2g_{2}x_{1} + 2f_{2}y_{1} + c_{2}}\)) = 0 + λ0 = 0
⇒ (x\(_{1}\), y\(_{1}\)) lies on (iii).
Similarly, it can be proved that the second point of intersection of the given circles also satisfy (i)
Hence, (iii) gives the family of circles passing through the intersection of the given circles.
In other words, the equation of any curve through the points of intersection of the circles (i) and (ii) is
(x\(^{2}\) + y\(^{2}\) + 2g\(_{1}\)x + 2f\(_{1}\)y + c\(_{1}\)) +
λ(x\(^{2}\) + y\(^{2}\) + 2g\(_{2}\)x + 2f\(_{2}\)y + c\(_{2}\))………………………..(iv)
⇒ (1 + λ)(x\(^{2}\) + y\(^{2}\)) + 2(g\(_{1}\) + g\(_{2}\)λ)x + 2(f\(_{1}\) + f\(_{2}\)λ)y + c\(_{1}\) + λc\(_{2}\) = 0
⇒ x\(^{2}\) + y\(^{2}\) + 2 ∙ \(\mathrm{\frac{g_{1} + g_{2}λ}{1 + λ}}\) x + 2 ∙ \(\mathrm{\frac{f_{1} + f_{2}λ}{1 + λ}}\)y + \(\mathrm{\frac{c_{1} + c_{2}λ}{1 + λ}}\) = 0 ………………………..(v)
If λ ≠ - 1, then equation (v) will represent the equation of a circle. Therefore, the equation (iv) represents the family of circles through the points of intersection of the circles (1) and (2).
Solved examples to find the equations of a circle through the points of intersection of two given circles:
1. Find the equation of the circle through the intersection of the circles x\(^{2}\) + y\(^{2}\) - 8x - 2y + 7 = 0 and x\(^{2}\) + y\(^{2}\) - 4x + 10y + 8 = 0 and passes through the point (-1, -2).
Solution:
The equation of any circles passing through the intersection of the circles S\(_{1}\) = x\(^{2}\) + y\(^{2}\) - 8x - 2y + 7 = 0 and S\(_{2}\) = x\(^{2}\) + y\(^{2}\) - 4x + 10y + 8 = 0 is S\(_{1}\) + λS\(_{2}\) = 0
Therefore, the equation of the required circle is (x\(^{2}\) + y\(^{2}\) - 8x - 2y + 7) + λ(x\(^{2}\) + y\(^{2}\) - 4x + 10y + 8) = 0, where λ (≠ -1) in an arbitrary real number
This circle passes through the point (-1, -2), therefore,
(1 + λ) + 4(1 + λ) + 4(2 + λ) + 4(1 - 5λ) + 7 + 8λ = 0
⇒ 24 - 3λ = 0
⇒ λ = 8
Now putting the value of λ = 8 in the equation (x\(^{2}\) + y\(^{2}\) - 8x - 2y + 7) + λ(x\(^{2}\) + y\(^{2}\) - 4x + 10y + 8) = 0 we get the required equation as 9x\(^{2}\) + 9y\(^{2}\) – 40x + 78y + 71 = 0.
2. Find the equation of the circle through the intersection of the circles x\(^{2}\) + y\(^{2}\) - x + 7y - 3 = 0 and x\(^{2}\) + y\(^{2}\) - 5x - y + 1 = 0, having its centre on the line x + y = 0.
Solution:
x\(^{2}\) + y\(^{2}\) - x + 7y - 3 + λ(x\(^{2}\) + y\(^{2}\) - 5x - y + 1) = 0, (λ ≠1)
⇒(1 + λ) (x\(^{2}\) + y\(^{2}\)) - (1 + 5λ)x + (7 - λ)y - 3 + λ = 0
⇒ x\(^{2}\) + y\(^{2}\) - \(\frac{1 + 5λ}{1 + λ}\)x - \(\frac{λ - 7}{1 + λ}\)y + \(\frac{λ - 3}{1 + λ}\) = 0 …………….(i)
Clearly, the co-ordinates of the centre of the circle (i) are [\(\frac{1 + 5λ}{2(1 + λ)}\), \(\frac{λ - 7}{2(1 + λ)}\)] By question, this point lies on the line x + y = 0.
Therefore, \(\frac{1 + 5λ}{2(1 + λ)}\) + \(\frac{λ - 7}{2(1 + λ)}\) = 0
⇒1 + 5λ + λ - 7 = 0
⇒ 6λ = 6
⇒ λ = 1
Therefore, the equation of the required circle is 2(x\(^{2}\) + y\(^{2}\)) - 6x + 6y - 2 = 0, [putting λ = 1 in (1)]
⇒ x\(^{2}\) + y\(^{2}\) - 3x + 3y - 1 = 0.
● The Circle
11 and 12 Grade Math
From Circle through the Intersection of Two Circles to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Oct 10, 24 05:15 PM
Oct 10, 24 10:06 AM
Oct 10, 24 03:19 AM
Oct 09, 24 05:16 PM
Oct 08, 24 10:53 AM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.